Predictability of Delayed Visual Feedback Under Rubber Hand Illusion Modulates Localization but Not Ownership of the Hand - Shibuya, Satoshi; Unenaka, Satoshi; Ohki, Yukari (Frontiers in Psychology, 2021)
The rubber hand illusion (RHI) is a perceptual illusion, whereby a fake hand is recognized as one’s own hand when a fake hand and felt real hand are stroked synchronously. RHI strength is mainly assessed using a questionnaire rating and proprioceptive drift (PD). PD is characterized by the proprioceptively sensed location of the participant’s own hand shifting toward the location of the fake hand after RHI. However, the relationship between the two measures of hand ownership and location remains controversial due to mixed findings: some studies report correlations between them, while others show that they are independent. Here, we demonstrated significant PD without RHI using delayed visual feedback. In this RHI study, video images of the fake hand were delivered to the subjects, and four delay intervals of visual feedback (80, 280, 480 and 680ms) were introduced. In four of six conditions, the delay interval was fixed throughout the condition. In the other two conditions, four delays were delivered in a predetermined order (i.e., serial condition, higher predictability) or in a pseudo-random order (i.e., random condition; low predictability). For the four conditions with a fixed delay, the questionnaire ratings and PD declined significantly when the delay interval exceeded circa 300ms. In both the serial and random conditions, no illusory ownership of the fake hand was reported in the questionnaire. In contrast, greater PD was found in the random condition but not in the serial condition. Our findings suggest that hand ownership and localization are caused by distinct multisensory integration processes.